2013
DOI: 10.1111/cen.12238
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in pubertal girls with type 1 diabetes: its relationship with glycaemic control, insulin resistance and hyperandrogenism

Abstract: In adolescent girls with diabetes, reduced HRV parameters are associated with worse glycaemic control, lower SHBG and higher weight SDS. SHBG should be considered in the cardiac risk models for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(59 reference statements)
1
20
1
Order By: Relevance
“…Obesity has been associated with reduced parasympathetic activity and a relative increase in sympathetic activity in adolescents with and without diabetes (10,19). In contrast, we found that there was no significant difference in BMI SDS in the ACR groups to explain heart rate variance differences between upper and lower ACR tertiles.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Obesity has been associated with reduced parasympathetic activity and a relative increase in sympathetic activity in adolescents with and without diabetes (10,19). In contrast, we found that there was no significant difference in BMI SDS in the ACR groups to explain heart rate variance differences between upper and lower ACR tertiles.…”
Section: Discussioncontrasting
confidence: 79%
“…Power spectral analyses of heart rate variability allow more sensitive detection of cardiac autonomic changes than the conventional Ewing battery of tests based on dynamic cardiovascular maneuvers (5,7,8). Recent studies using these modern methods have demonstrated that adverse changes in heart rate variability may be detected during adolescence in people with type 1 diabetes and are primarily associated with poor glycemic control (1,9,10). However, there is a paucity of data on whether cardiac autonomic function is associated with early renal dysfunction before the onset of microalbuminuria.…”
mentioning
confidence: 99%
“…Girls seem to be more at risk of overweight, a recognized risk factor for later development of eating disorders . In association with increased weight, there is also the risk of ovarian hyperandrogenism, hirsutism, and polycystic ovarian syndrome . In a recent study of adolescents with hyperandrogenism and type 1 diabetes, metformin treatment significantly decreased serum androgens compared to placebo.…”
Section: Growth Weight Gain and Pubertal Developmentmentioning
confidence: 99%
“…Six addressed fertility issues and eighteen addressed menstrual cycle characteristics of type 1 diabetes but were unrelated to androgen excess ( Fig. 1 and Supplementary Data), leaving seventeen original articles dealing with androgen excess (8)(9)(10)(11)(12)(13)(14)(15)(16)(24)(25)(26)(27)(28)(29)(30)(31). Only 9 of these 17 articles contained data about the prevalence of PCOS and related traits (8,(10)(11)(12)(13)(14)(15)(16)28) and were included in the meta-analyses.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%